The Impact of E-Commerce Strategies on Firm Value : Lessons from Amazon.com and its Early Competitors - Darren Filson (Claremont McKenna College, Department of Economics, 2003)
Which strategies generate value in e-commerce environments? In a step towards answering this question, this paper estimates the impacts of several competitive strategies on the values of the well-known Internet retailer Amazon.com and three of its early competitors, BarnesandNoble.com, CDNOW, and N2K, from their IPO dates until exit or the end of 2001. The strategies analyzed include alliance formation, offline expansion, pricing, product line expansion, and service improvement. The results provide insight into the usefulness of various ways of competing online and could be applied in other settings where firms enter new environments about which they have little information.
Keywords: L21; D81; G31; M21; L81; 330; Competitive Advantage; Competitive Strategy; Event Studies; Internet; Valuation; E-Business; Strategische Unternehmensplanung; Wettbewerbsstrategie; Unternehmenswert; Buchhandel; Vereinigte Staaten